Unusual Cushing’s Syndrome and Hypercalcitoninaemia due to a Small Cell Prostate Carcinoma - Antonio Balestrieri; Elena Magnani; Fiorella Nuzzo (Case Reports in Endocrinology)
A 75-year-old man was hospitalized because of severe hypokalaemia due to ACTH dependent Cushing’s syndrome. Total body computed tomography (TBCT) and 68 Gallium DOTATATE PET/CT localized a voluminous prostate tumour. A subsequent transurethral prostate biopsy documented a small cell carcinoma positive for ACTH and calcitonin and negative for prostatic specific antigen (PSA) at immunocytochemical study; serum prostatic specific antigen (PSA) was normal. Despite medical treatments, Cushing’s syndrome was not controlled and the patient’s clinical condition progressively worsened. Surgical resection was excluded; the patient underwent a cycle of chemotherapy followed by febrile neutropenia and fatal intestinal perforation. This case report describes a rare case of Cushing’s syndrome and hypercalcitoninaemia due to a small cell carcinoma of the prostate, a rare tumour with very few therapeutic options and negative prognosis.